Analisis Pengelolaan Surat Masuk Dan Surat Keluar Di Dinas Kependudukan Dan Pencatatan Sipil Provinsi Sumatera Utara - Irma Yunita; Zainarti Zainarti (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
The purpose of this study was to determine the management of incoming and outgoing mail and the obstacles in the management of incoming and outgoing mail. In this study using a qualitative method. Interviews, observations, and literature studies were used to obtain data in this study. The conclusions in this study are: (1) Management of incoming mail: (a) Receipt of letters, (b) Recording of letters, (c) Attachment of Disposition Sheets, (d) Directions to Management, (e) Follow-up, (f) Storage. (2) Management of outgoing mail: (a) Drafting of Letters, (b) Tiered Approval, (c) Numbering, (d) Distribution, (e) Storage. (1) Barriers to management of incoming mail: (a) Receipt and Processing Time of Letters, (b) Leaders who are on Overseas or Overseas Service Tasks, (c) Difficulty in finding letters because they are still using the agenda book system, (d) Loss of letters - a letter that should be archived. (2) Obstacles in managing outgoing mail: (a) Error in numbering outgoing letters to be sent, (b) Anti-datir letters are sometimes still used in making outgoing letters.